2022
DOI: 10.1155/2022/3575457
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Three-Way Decision Model for Improving Computational Thinking Based on Grey Correlation Analysis

Abstract: Computational thinking (CT) is an approach that applies the fundamental concepts of computer science to solve problems, design systems, and understand human behavior, which can help students develop lifetime learning and generate new topics. It has been the elements of competency expected of the next generation of talents. However, the current research on computational thinking evaluation is still at a relatively weak stage. The existing related evaluation research is still limited to traditional curriculum ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…It is beneficial to visualize learners’ thinking performance process by comparing high- and low-scoring groups (Sun et al, 2022). Distinguishing students with high and low CT scores can help instructors conduct individualized teaching for students to effectively improve their CT skills (Xu et al, 2022). Previous studies (Hsu et al, 2023; Wei et al, 2020) have indicated the differences in the CT skills of high- and low-scoring groups of students in programming learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is beneficial to visualize learners’ thinking performance process by comparing high- and low-scoring groups (Sun et al, 2022). Distinguishing students with high and low CT scores can help instructors conduct individualized teaching for students to effectively improve their CT skills (Xu et al, 2022). Previous studies (Hsu et al, 2023; Wei et al, 2020) have indicated the differences in the CT skills of high- and low-scoring groups of students in programming learning.…”
Section: Literature Reviewmentioning
confidence: 99%